Host Resistance and Temperature-Dependent Evolution of Aggressiveness in the Plant Pathogen Zymoseptoria tritici - Chen, Fengping; Duan, Guo-Hua; Li, Dong-Liang; Zhan, Jiasui (Frontiers in Microbiology, 2017)
Understanding how habitat heterogeneity may affect the evolution of plant pathogens is essential to effectively predict new epidemiological landscapes and manage genetic diversity under changing global climatic conditions. In this study, we explore the effects of habitat heterogeneity, as determined by variation in host resistance and local temperature, on the evolution of Zymoseptoria tritici by comparing the aggressiveness development of five Z. tritici populations originated from different parts of the world on two wheat cultivars varying in resistance to the pathogen. Our results show that host resistance plays an important role in the evolution of Z. tritici. The pathogen was under weak, constraining selection on a host with quantitative resistance but under a stronger, directional selection on a susceptible host. This difference is consistent with theoretical expectations that suggest that quantitative resistance may slow down the evolution of pathogens and therefore be more durable. Our results also show that local temperature interacts with host resistance in influencing the evolution of the pathogen. When infecting a susceptible host, aggressiveness development of Z. tritici was negatively correlated to temperatures of the original collection sites, suggesting a trade-off between the pathogen’s abilities of adapting to higher temperature and causing disease and global warming may have a negative effect on the evolution of pathogens. The finding that no such relationship was detected when the pathogen infected the partially resistant cultivars indicates the evolution of pathogens in quantitatively resistant hosts is less influenced by environments than in susceptible hosts.